The Effect of Negative, Positive, and Neutral Self-imagery on Symptoms and Processes in Social Anxiety Disorder - Ng, Ashlen S.; Abbott, Maree J. (Cognitive therapy and research, 2016)
Cognitive models of social anxiety disorder suggest that negative self-images maintain social fears despite repeated exposure to benign social situations. An accumulating body of evidence supports this notion, and preliminary data indicates that modifying self-imagery can potentially reduce fears of negative evaluation in socially anxious individuals. The present study examined the effects of negative, positive, and neutral self-imagery during a speech task in 49 clinically diagnosed and 41 non-clinical participants. The impact of self-imagery on various symptoms and both cognitive and attentional processes proposed by cognitive models was empirically tested in a two group by three condition between-subjects experimental design. Expected group differences emerged with regard to symptom, affective, and cognitive measures, as well as performance discrepancy scores; however, specific statistical interactions hypothesised between group and condition were not supported for the majority of symptom measures, suggesting that negative imagery may not be differentially influential, as posited by current theoretical models. Continuing research is warranted to further disentangle the relative importance of different aspects of self-imagery in order to better understand the factors that maintain social threat fears, and inform clinical intervention research modifying imagery in effective treatments for social anxiety disorder.